2000
DOI: 10.1177/1077727x00291004
|View full text |Cite
|
Sign up to set email alerts
|

Menu Planning, Food Consumption, and Sanitation Practices in Day Care Facilities

Abstract: This research aimed to assess the nutritional quality of diets as well as food safety and sanitation issues in child day care settings. More than 100 day care facilities participated in a comprehensive needs assessment and on‐site visit. Data were collected regarding nutritional content of menus, compliance with Child and Adult Care Food Program guidelines, food consumption by children, and food safety and sanitation practices. Written menus submitted by the facilities exceeded 67% of Recommended Dietary Allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Although the percentage of intervention centres that met most of the guidelines improved, these improvements were not statistically significant. Similar results were noted in an earlier pilot study in Saskatchewan childcare centres ( Chow et al, 2016 ), which is consistent with several American and Australian studies ( Erinosho et al, 2011 , Finch et al, 2018 , Grady et al, 2018 , Hardy et al, 2010 , Kuratko et al, 2000 ). Future research should address the barriers that prevent childcare providers from following applicable guidelines.…”
Section: Discussionsupporting
confidence: 91%
“…Although the percentage of intervention centres that met most of the guidelines improved, these improvements were not statistically significant. Similar results were noted in an earlier pilot study in Saskatchewan childcare centres ( Chow et al, 2016 ), which is consistent with several American and Australian studies ( Erinosho et al, 2011 , Finch et al, 2018 , Grady et al, 2018 , Hardy et al, 2010 , Kuratko et al, 2000 ). Future research should address the barriers that prevent childcare providers from following applicable guidelines.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies observed deviations from meal patterns, unrecorded substitutions from planned menus or unconsumed food in CACFP-participating settings. For example, a study of participating homes and centers in Texas found that no provider always adhered to the CACFP meal patterns, and the only meal components served 100% of the time were milk at breakfast and meat at lunch (Kuratko, Martin, Lan, Chappell, & Ahmad, 2000). In a study of Head Start centers, only four of 269 meals perfectly matched menu descriptions (Fleischhacker et al, 2006).…”
Section: Potential Mechanisms Linking Cacfp To Children's Nutritionalmentioning
confidence: 99%
“…5 However, other studies that observed the meals served in CACFP-participating settings reveal that meal patterns are sometimes not followed; substitutions from planned menus are not documented, or children do not consume the food served. One study of participating homes and centers in Texas found that no provider met the meal patterns all of the time, and the only meal components served 100% of the time were milk at breakfast and meat at lunch (Kuratko et al 2000). In a study of Head Start centers, only four meals served out of 269 perfectly matched menu descriptions (Fleischhacker et al 2006).…”
Section: Cacfp Participation and Child Nutritional Outcomesmentioning
confidence: 99%